Teaching materials for higher education in conditions development of the information technology industry - Kapiton, Alla; Poliakova, Oksana; Ilnytska, Ganna (Олді+, 2022)
The use of innovative teaching methods in the development of information and telecommunications technologies in the educational process of higher education provides an opportunity to significantly improve the quality of training of future professionals. The need to introduce innovative teaching methods in the credit-module system in the process of professional training of future professionals, using modern technological capabilities, requires further research and development.
Keywords: higher education; the information technology industry; information society; information technology; training of specialists; software